PLANNING AND PRESENTING AN INFORMATIVE SPEECH - Qadirova Dilnura (TADQIQOTLAR.UZ, 2023)
Abstraction. Informative speaking offers you an opportunity to practice your researching, writing, organizing, and speaking skills. You will learn how to discover and present information clearly. If you take the time to thoroughly research and understand your topic, to create a clearly organized speech, and to practice an enthusiastic, dynamic style of delivery, you can be an effective "teacher" during your informative speech. Finally, you will get a chance to practice a type of speaking you will undoubtedly use later in your professional career. The purpose of the informative speech is to provide interesting, useful, and unique information to your audience. By dedicating yourself to the goals of providing information and appealing to your audience, you can take a positive step toward succeeding in your efforts as an informative speaker.